UiTM collaborative with Department of Forestry of Peninsular Malaysia (JPSM) - UiTM, UGC (UiTM Green Centre, 2025)
SHAH ALAM, OCTOBER 23, 2025 - Site Visit for a collaborative project of UiTM with the Department of Forestry of Peninsular Malaysia (JPSM). This strategic collaboration is to improve the green areas within the UiTM and the new recreation area.